Comparability of subcutaneous and sublingual immunotherapy outcomes in allergic rhinitis clinical trials - Calderón, Moisés A.; Pfaar, Oliver (Current opinion in allergy and clinical immunology, 2012)
Purpose of review: To conduct a qualitative comparison between the primary and secondary outcomes used in clinical trials of subcutaneous immunotherapy (SCIT) and sublingual immunotherapy (SLIT) for allergic rhinitis. Recent findings Studies of SCIT and SLIT for allergic rhinitis published up to January 2012 were included in this systematic review. Different ways of defining primary and secondary outcome parameters in studies investigating specific immunotherapy are described. Whereas older studies often use the total symptom score and the total medication score individually for the primary efficacy analysis, more recent studies follow current international recommendations of applying the total combined score as primary outcome measure. Even wider is the range of secondary outcomes in clinical trials with few being validated or standardized. Summary: As already recognized as a major concern in recent literature, standardized and validated primary endpoints are of paramount importance in order to improve the comparability of study results. The lack of consistency in the selection of primary outcome parameters represents a major problem when comparing the same therapeutic intervention. A main point of concern is the absence of validation data for those primary and secondary outcomes selected. In conclusion, the qualitative analysis of well powered studies confirms an urgent call from academics, regulatory agencies and the pharmaceutical industry for validated primary outcome parameters and standardized definitions.
Gesehen am 22.06.2018